(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article examines the history of the development of American society, in which there is a wide range of cultural diversity. American society has historically evolved as a society of immigrants , and includes many ethnicities with their own specifi c features. The article provides a historical overview of the development of the American multinational company to put into practice the idea of «melting pot», to the evolution of the concept of multiculturalism in «ethnic mosaic». Particular attention is paid to the problem of national minorities and the «color» of the population, as well as their struggle for the realization of their civil rights. Also examines the features and consequences of the American policy of multiculturalism, his criticism and achievements. Key words: immigrant,t multiculturalism, segregation, «melting pot», «ethnic mosaic» civil rights.